1989
DOI: 10.1530/jrf.0.0870479
|View full text |Cite
|
Sign up to set email alerts
|

High survival rate of unfertilized mouse oocytes after vitrification

Abstract: Unfertilized mouse oocytes were cooled rapidly by directly plunging them into liquid nitrogen, immediately after exposure to a highly concentrated solution (modified VS1: 2.53 M-dimethyl sulphoxide, 2.36 M-acetamide, 1.19 M-propylene glycol, 5.4% (w/v) polyethylene glycol (Mr 8000) in PB1), and later warmed in a 37 degree C waterbath. After warming, 305 out of 348 oocytes (87.6%) were morphologically normal. After fertilization in vitro of cryopreserved oocytes, the proportions of pronuclear oocytes and 2-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(66 citation statements)
references
References 10 publications
(10 reference statements)
3
60
0
3
Order By: Relevance
“…They found that the addition of an amide to McjSO mitigated its toxicity (3,5,6,9). As a result, investigators have used amides to reduce the toxicity of McjSO in a variety of systems, such as rat kidney renal cortex (3), rabbit renal cortex (5, 6), porcine blastocysts (36), rat blastocysts (19), bovine oocytes (10), mouse oocytes (22,24), and mouse embryos (23). Thus it seemed promising to use amides in zebrafish embryos.…”
mentioning
confidence: 99%
“…They found that the addition of an amide to McjSO mitigated its toxicity (3,5,6,9). As a result, investigators have used amides to reduce the toxicity of McjSO in a variety of systems, such as rat kidney renal cortex (3), rabbit renal cortex (5, 6), porcine blastocysts (36), rat blastocysts (19), bovine oocytes (10), mouse oocytes (22,24), and mouse embryos (23). Thus it seemed promising to use amides in zebrafish embryos.…”
mentioning
confidence: 99%
“…This auther has previously demonstrated that unfertilized mouse oocytes from F1 hybrid strain can be cryopreserved successfully using the method of ultrarapid freezing [4].…”
Section: %mentioning
confidence: 99%
“…Treatment with CPA induced a transient rise of intracellular free calcium level, premature exocytosis of cortical granules, and hardening of zonae pellucidae [7,8]. Application of vitrification improved the efficacy of oocyte cryopreservation, especially in mice [9,10] and humans [11,12]. However, vitrification of oocytes from large domestic species enriched with cytoplasmic lipid droplets still requires substantial improvement [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%